Optimizing Spare Parts Procurement to Enhance Plant Availability - Triwidodo, Stepanus Ady; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2013)
During operation all equipments in Plant need spare part to replace its damage element to maintain Plant Availability. Variation in spare part, spare partÃ¢â‚¬â„¢s life service, and procurement lead time tend to increase number of spare part request. On the other hand, huge number of inventories has no direct correlation with plant availability as the fact that many break-down equipment need extended repair time due to unavailable spare part. Inventory also became main topic on company performance especially on financial side. This paper will discuss spare part procurement method on Steel Making Plant that projected able to maintain and increase Plant Availability and concern to inventory level. The working method started by spare part classification, inventory policy for each spare part classification, and procurement method. Spare part classification according to three mains criteria, which are: usage value, critically, and usage frequency. Spare part will divide by 27 different classes to decide inventory policy. These are three inventory policies:Ã‚Â with-out stock, one piece stock, and more pieces stock. Spare part procurement method should able to support defined inventory policy and concern to vendor availability. There are some spare part procurements method alternatives that have individually strong and weak point.Ã‚Â For evaluate spare part procurement method use Ã¢â‚¬Å“Kepner-Tregoe Decision AnalysisÃ¢â‚¬Â and to analyze potential problem that may rise from chossen procurement method is Ã¢â‚¬Å“Adverse ConsequencesÃ¢â‚¬Â.Ã‚Â Keywords: spare part, equipment availability, inventory, spare part classification, inventory policy, spare part procurement method.